Editorial: Genetic association studies in oilseeds - Shobhana, V.G.; Kirubakaran, Silvas J. P.; Li, Song; Parthiban, T.P. (Frontiers Media, 2024)
Crop improvement traits that are significant for agriculture are genetically complex and regulated by polygenes. These polygenes are spread across crop genomes and mapped as genomic targets known as quantitative trait loci (QTLs). Genome-Wide Association (GWA) mapping is an effective plant breeding strategy for detecting natural allelic variations and associating haplotype polymorphisms with valuable agronomic traits such as yield, (a) biotic resistance, and nutritional quality traits. GWA has gained momentum over traditional mapping by documenting alleles/QTLs with a higher resolution by addressing the population structure and linkage disequilibrium (LD). The success of GWA relies on the germplasm choice, population size and diversity, molecular marker density, accurate phenotypic data, and appropriate statistical analyses. The biological value of the genomic regions identified by QTL or GWA warrants validation through diverse functional genomic approaches that drive crop improvement in commercial crops. Combining mapping and functional genomic strategies will enhance the use of genetic variation to improve economically valuable traits of crop plants. Association mapping studies in oilseed crops are at an early stage and are accelerating at a faster pace. Association mapping would unquestionably find genomic solutions to mitigate losses caused by both biotic and abiotic factors, with the success of identifying true associations depending on the marker with higher association signals and their positions within LD.